Psalm 137 : exile - not the time for singing the Lord's song - Mare, Leonard P. (Old Testament Essays, 2010)
The experience of exile is not confined to the pages of the Bible dealing with the Babylonian exile. Exile is not only a geographical place, but it is a religious state of mind. Although the Jews were geographically displaced, their biggest experience of exile was their loss of the structured, reliable world which provided them with meaning. Exile is thus primarily not a geographical issue, but it is a social, moral, cultural, liturgical and spiritual issue; an understanding that one is in a hostile, alien situation. The purpose of this paper is to analyse Psalm 137 to ascertain what Israel's response was in a time of exile. How did they address the faith crisis of exile? How did they react to the loss of their world, their temple, their homeland, their security? Did they continue to worship in a strange land, and if so, how? A second purpose of the paper will then be to establish what the proper response of contemporary worshippers during times of exile should be.
free